The conceptual model of construction and real estate negotiation - Urbanavičienė, Vita; Kaklauskas, Artūras; K. Zavadskas, Edmundas (International Journal of Strategic Property Management, 2009)
Negotiations are common in many activities; the sectors of construction and real estate are not an exception: here the negotiations are an inseparable part of the real estate buying and selling process. The article analyses scientific research related to negotiations and presents the developed model for multiple criteria analysis of construction and real estate negotiations. The analysis of the negotiation processes in construction and real estate and the analysis of the relevant support for decision‐making in negotiations must be thorough; it must consider not only economic but also political, legal, socio‐cultural, psychological, consumer behaviour, technological, quality of life and other issues. The developed model enables to analyse the combination of the real estate negotiation process, the improvement of its efficiency through use of decision support and voice stress analysis technology and the participating stakeholder groups seeking their goals together with the influencing external macro and micro environment. The paper dwells on the components of this model. First Publish Online: 18 Oct 2010